Mass Housing in the Socialist City. Heritage, Values, and Perspectives. Case Studies in Germany, Russia, and Ukraine. - (:unkn) unknown (DOM, 2019)
Mass housing in Germany, Russia, and Ukraine represents an enormous volume of housing today and therefore an important tool for the future development of cities. But transformation of these districts is needed due to the functional, societal, and technical challenges they face. How can sustainable, socially compatible, ecologically responsible, and economically efficient development be achieved? This book summarises the results of a three-year research project. Based on the selected case studies, it points out the qualities and values as well as the problems and possibilities involved in spatially transforming prefabricated housing estates from the 1960s and 1970s. The specific features and characteristics of the socialist city are evaluated with respect to their potentials and difficulties, and with regard to the requirements placed on future district planning and development. Hence this book contributes to the on-going discussion and serves as a valuable basis for developing planning strategies.
Keywords: Wohnsiedlung; Großwohnsiedlung; Massenwohnungsbau; Städtebau; Industrielles Bauen; Großplattenbauweise; Architektur(sozialistisch); Stadtquartier; Wohnumfeldqualität; Internationaler Vergleich